Emergence of Leuconostoc mesenteroides as a causative agent of oozing in carrots stored under non‐ventilated conditions - Lampert, Yael (Microb Biotechnol, 2017)
Long‐term storage and transport of post‐harvest carrots (Daucus carota L.) require a low‐temperature, high‐relative‐humidity environment, usually with low ventilation. Following long‐term storage, a slimy exudate (oozing) often appears on the carrots, leading to severe spoilage. We characterized the environmental conditions leading to these symptoms and identified the causative agent. Simulation of non‐ventilated storage conditions revealed accumulation of CO (2) (to 80%) and ethanol (to 1000 ppm); then, a transparent exudate appeared on the carrot surface which, upon ventilation, developed into tissue browning and soft rot. Peels from oozing carrots contained over 10‐fold the total bacterial counts of healthy carrots. The total peel microbiome was determined by 16S rDNA sequencing. During oozing stage, the surface of carrots incubated in a CO (2)‐rich (98%) environment harboured a bacterial population dominated by Lactobacillales and Enterobacteriales, differing markedly from those incubated in air. Three prevalent bacterial isolates from the oozing carrots were identified as Pantoea agglomerans, Rahnella aquatilis and Leuconostoc mesenteroides. Inoculation of carrot discs with L. mesenteroides, but not the others, induced oozing under high CO (2), suggesting that this bacterium is responsible for oozing of stored carrots. These findings should enable development of approaches to preventing carrot spoilage during long‐term storage.